Engineering Safety Analysis via Destructive Numerical Experiments - Haug, E. (Engineering Transactions, 1981)
The paper is devoted to an overview of the numerical analysis of crash, impact, penetration, perforation and explosion problems which may arise in the safety consideration of automotive, naval, aerospace, nuclear and civil engineering industries. It first discusses methodologies as they have been applied to various fields of interest, stressing the success of mixed approaches where initial physical and numerical analyses for program validation are equally important. Modern numerical methods are briefly discussed and typical examples of problems solved in the mentioned categories are also given.